Diogenes Syndrome: Identification and Distinction from Hoarding Disorder - Proctor, Carmel; Rahman, Sakib (Case Reports in Psychiatry, 2021)
“Severe domestic squalor” or Diogenes syndrome is characterised by extreme self-neglect of environment, health, and hygiene, excessive hoarding, squalor, social withdrawal, and a distinct lack of concern or shame regarding one’s living condition. This report presents a case of a 51-year-old male admitted to the hospital psychiatric ward following the police removing him from his home. Police officers attended the man’s home following the alarm being raised by his stepfather that he had not been seen or heard from in 3 weeks. His home was covered in several feet of rubbish, rotting food, and debris and smelled intensely of rotting mould, urine, and faeces. He was found lying nude on top of garbage with a rug over him. Diogenes syndrome is highly comorbid with psychiatric and somatic disorders, including depression, obsessive-compulsive disorder, personality disorder, and stress. This case report provides a rare opportunity to better understand the distinction of Diogenes syndrome from the closely related condition hoarding disorder. Furthermore, creating an agreed-upon constellation of symptoms representative of Diogenes is essential to creating a formal Diagnostic and Statistical Manual of Mental Disorders (DSM) entry, which would facilitate the much-needed development of assessment measures to enable accurate diagnosis and treatment.